Sosialisasi Penggunaan Buku Panduan Website Padukuhan Watubelah, Desa Kemadang, Kapanewon Tanjungsari, Gunung Kidul: Pengabdian - Dismas Persada Dewangga Pramudita; Putra Palampang Tarung; Definely Annisa Firdaus; Priestly Tanisan Manashe; Juneva Drupadi Putri; Ignatius David Djwa; Stefanus Wijayanto; Melania Dnanti Ceintanu Dimar; Bernadetta Fitya Halawa; Jovanothy Kevin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The digital transformation at the village and hamlet levels has become a strategic necessity for strengthening governance, increasing transparency, and expanding access to public information. This community service program aims to enhance the capacity of the Watubelah Hamlet apparatus in managing the official website (watubelah.com) through the dissemination of an operational website guide module, technical training, and intensive assistance for the hamlet administrators. The methods used include socialization, direct demonstrations, hands-on practice of key website features, and simulations of public information management. The results of the program indicate strong enthusiasm and improved abilities among the hamlet apparatus in operating the admin dashboard, updating news, managing the organizational structure, updating hamlet information, showcasing local potential, and interacting with the community through incoming messages. The existence of the hamlet website has proven to be an effective medium for strengthening community communication and supporting local government transparency. This program contributes to enhancing digital literacy among village communities and ensures the sustainability of independent website management by the hamlet apparatus.